A working model for estimating CO2-induced uplift of cap rocks under different flow regimes in CO2 sequestration - Gravanis, Elias; Sarris, Ernestos (My University, 2023)
In this work we study the deflections of an impermeable caprock in the various flow regimes of the plume evolution in the CO2 sequestration problem. The pressure distributions causing the deflections are determined by three different ways: via CFD simulations, known analytical solutions and a novel model based on mass conservation (plug flow model). We find that the different approaches for calculating the deflections are in very good agreement exhibiting minor deviations near the well; the overall deviations also grow slowly with time. We also find that the magnitude of deflections is inversely proportional to the gravity number, that is, large deflections correspond to the low buoyancy regime. These findings suggest that the deflections are mainly driven by the injected volume of CO2, a fact which is naturally built in the proposed model, dictating a piecewise logarithmic pressure profile which greatly facilitates analytical treatment of the deflection field calculations. This methodology can be used for predicting deflections with relative ease that are useful for caprock uplift and integrity considerations.
Keywords: CO2 injection; Buoyancy effects; Surface uplift; Caprock deflections; Thin plate theory; Analytical solutions